Theoretical-methodological approach for a determination of a special prise of particularly attractive railway objects - Gnennyj, O. N. (Science and Transport Progress, 2012)
For the enterprises of railway transport the question of an assessment of objects of real estate on non-market base, including, determination of special value is actual. In work the theoretical-methodological approach for determination of a special cost of an assessment as bags of its market cost is developed. The extra charge to market cost is defined by a way of capitalization of the additional net operating income defined as a difference between special and market by the net operating income. In article methods of determination of the special net operating income are developed.